Design and development of thyroxine/heparin releasing affordable cotton dressings to treat chronic wounds. (4th March 2022) - Waris, Tayyba Sher; Shah, Syed Tahir Abbas; Mehmood, Azra; Iqbal, Zohaib; Zehra, Mubashra; Chaudhry, Aqif Anwar; Rehman, Ihtesham Ur; Yar, Muhammad
Abstract: This research on a thyroxine/heparin‐based cotton wound dressing tests angiogenic and wound healing ability of thyroxine/heparin in a chick chorionic allantoic membrane bioassay and in skin wounds in healthy rats. Commercially available cotton dressings were simply loaded with thyroxine/heparin solutions and coated with wax. Prior to undertaking the animal study, we assessed in vitro release of thyroxine/heparin from coated and uncoated cotton dressings. Both showed more than 85% release of drug over 14 days, though the lesser release was observed in wax‐coated thyroxine/heparin dressing as compared to uncoated thyroxine/heparin dressing. Testing of angiogenesis through CAM assay proved good angiogenic potential of heparin and thyroxin, but the thyroxine found more angiogenic than heparin. In animal study, full‐thickness skin wounds of 20 mm diameter showed good healing in both heparin and thyroxine‐treated groups. But the most striking result was seen in the thyroxine‐treated group where thyroxine showed significant difference with heparin‐treated group and completely healed the wounds in 23 days. Thus, the study suggest that thyroxine possesses greater angiogenic and wound healing potential than heparin, and the use of thyroxine/heparin‐loaded wax‐coated cotton dressing could be a cost‐effective option for the management of chronic wounds.